2018
DOI: 10.2337/dc17-2123
|View full text |Cite|
|
Sign up to set email alerts
|

Why Are We Failing to Address the Issue of Access to Insulin? A National and Global Perspective

Abstract: Insulin was discovered in 1921 and soon became widely available in high-income countries. However, many people currently in need of this life-saving medicine are unable to access it. This is a global phenomenon, impacting not only populations of low- and middle-income countries but low-income populations in the U.S. In the U.S., the rate of diabetic ketoacidosis remains high in certain subpopulations, the cost of insulin being the main precipitating factor. On a global level the main cause of mortality for a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…Recently price reductions as great as 70% have been seen for biosimilar infliximab. 39 Price reductions for the first insulin biosimilar available in the USA or Europe—a biosimilar of insulin glargine—have also arguably been modest (a second biosimilar has been approved in the European Union in the past few months, but pricing data are not yet available), 40 although large price reductions would not be expected with the first non-originator market entrant. As a point of comparison, the price estimated in this analysis for insulin glargine is about 60%–80% lower than prices of originator insulin glargine in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Recently price reductions as great as 70% have been seen for biosimilar infliximab. 39 Price reductions for the first insulin biosimilar available in the USA or Europe—a biosimilar of insulin glargine—have also arguably been modest (a second biosimilar has been approved in the European Union in the past few months, but pricing data are not yet available), 40 although large price reductions would not be expected with the first non-originator market entrant. As a point of comparison, the price estimated in this analysis for insulin glargine is about 60%–80% lower than prices of originator insulin glargine in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, several international studies dealt with the estimation of costs for treating diabetes (16)(17)(18)(19)(20)(21)(22)(23), pointing out several issues. Whereas in low-and middle-income countries, inadequate access to insulin (24,25) and oral drugs for controlling glucose and blood pressure represent the main bottleneck in type 2 diabetes treatment; in high-income countries, main problems concern with lifestyle and are related to nutrition, exercise habits and obesogenic living environments (26). Evidence demonstrated that type 2 diabetes is potentially reversible (27,28) and that early diagnosis and higher participation of patients in disease management could reverse current trends (29).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, many people struggle financially to support their insulin needs. [17][18][19] RHI is much less expensive than many rapid-acting insulin analogs, 17,18 and trial data suggest that patients with T2D may be appropriately controlled on human insulin. 17,20 Nonetheless, while rapidacting insulin products are approved for use in insulin pumps, 21,22 RHI is not approved or recommended for pump use according to manufacturers' drug labeling.…”
mentioning
confidence: 99%